Development E-Learning Using Problem Based Learning - R Febriana; R Yusri; H Delyana (Pascasarjana Universitas Pendidikan Indonesia, 2019)
Inadequate textbooks, difficult language to understand and student’s low motivation became causing student scores on space geometry lectures to be low. This study aimed to develop problem-based learning based e-learning. The development used Plomp model consisting of 3 phases namely preliminary research, prototyping phase, and assessment phase. Those materials in e-learning were all materials existing Problem-Based Learning of Space Geometry module that were valid and practical. The instruments used were validity sheets, practical sheets and questionnaires. Data analysis technique used was descriptive qualitative and quantitative. The research shows that those contents of the module integrated into e-learning are categorized into valid and practical and result of Information and Technology expert validation states that requirements should exist in e-learning have also been fulfilled both in terms of construction and content.